The Intellectual Consequences of Religious Heterodoxy, 1600-1750 - Mortimer, Sarah; Robertson, John. (Leiden : BRILL, 2012)
Challenging the common assumption that religious heterodoxy was a prelude to the secularisation of thought, this volume explores the variety of relations between heterodox theology, political thought, moral and natural philosophy and historical writing in both Protestant and Catholic Europe from 1600 to the Enlightenment.
Between Orthodoxy and Heterodoxy in Italian Culture in the Early 1700s: Giambattista Vico and Paolo Mattia DoriaConyers Middleton: The Historical Consequences of Heterodoxy; David Hume's Natural History of Religion (1757) and the End of Modern Eusebianism; Bibliography; Index.
Description based on print version record.
Keywords: Church history -- 17th century -- Congresses; Church history -- 18th century -- Congresses; Heresy -- History -- 17th century -- Congresses; Heresy -- History -- 18th century -- Congresses; Intellectual life -- 17th century -- Congresses; Intellectual life -- 18th century -- Congresses; Religion; RELIGION / History; Heresy -- History -- 17th century -- Congresses; Heresy -- History -- 18th century -- Congresses; Intellectual life -- 17th century -- Congresses; Intellectual life -- 18th century -- Congresses; Church history -- 17th century -- Congresses; Church history -- 18th century -- Congresses; Electronic books